Strategy for Building Communication Skills and Self-Confidence in Public Speaking Learning Through Lectures - Jaizul W, Alim; Sandi S, Renda (International Journal of Linguistics, Communication, and Broadcasting, 2024)
Public speaking is an important communication skill in various contexts, both in academic, professional, and social environments. This study aims to identify strategies that can be used in public speaking learning through lectures, with a focus on developing communication skills and self-confidence. The literature review shows that lectures as a teaching method can be enhanced by techniques such as speaking simulations, providing practical examples, constructive feedback, and a gradual approach starting from small groups to larger audiences. These strategies have been shown to be effective in reducing public speaking anxiety and helping participants hone their communication skills. The results of this study are expected to contribute to the development of more effective and in-depth public speaking learning in various educational institutions.